Embracing open science agenda through coordinated approach: The Botswana case - Ntlotlang, Tuelo (Cadernos BAD, 2020)
A number of countries around the world have embraced the open science agenda. However, in some cases, existing legislative frameworks in most countries typically do not allow much openness of data and science. Botswana is an example of such countries. The absence of legislative framework poses a challenge to librarians, researchers and policy makers with regard to data sharing. This has derailed the country’s development in terms of innovation and creativity. This issue has prompted different stakeholders to come together to work towards changing the current systems and regulatory frameworks in relation to open science and data management. The Botswana Open Data Open Science (ODOS) national committee was established in 2017 by different stakeholders being public bodies, business communities, information professionals and research communities to develop an open data open science policy that would enable data sharing and openness in science within the country. The purpose of this paper is to share the strategies used to establish inclusive interactions and engagement between stakeholders in facilitating the open data readiness implementation in Botswana. Moreover, the paper will highlight challenges encountered and achievement attained through this collaborative effort.